Alzheimer's disease cerebrospinal fluid biomarkers predict cognitive decline in lewy body dementia - Abdelnour, Carla; van Steenoven, Inger; Londos, Elisabet; Blanc, Frédéric; Auestad, Bjørn; Kramberger, Milica G.; Zetterberg, Henrik; Mollenhauer, Brit; Boada, Mercè; Aarsland, Dag (Movement disorders, 2016)
ABSTRACT Introduction Alzheimer's disease pathologies are common in dementia with Lewy bodies, but their clinical relevance is not clear. CSF biomarkers amyloid beta 1‐42, total tau, and tau phosphorylated at threonine 181 reflect Alzheimer's disease neuropathology antemortem. In PD, low CSF amyloid beta 1‐42 predict long‐term cognitive decline, but little is known about these biomarkers as predictors for cognitive decline in Lewy body dementia. The aim of this study was to assess whether Alzheimer's disease CSF biomarkers predict cognitive decline in Lewy body dementia. Methods From a large European dementia with Lewy bodies multicenter study, we analyzed baseline Alzheimer's disease CSF biomarkers and serial MMSE (baseline and 1‐ and 2‐year follow‐up) in 100 patients with Lewy body dementia. Linear mixed‐effects analyses, adjusted for sex, age, baseline MMSE, and education, were performed to model the association between CSF biomarkers and rate of cognitive decline measured with MMSE. An Alzheimer's disease CSF profile was defined as pathological amyloid beta 1‐42 plus pathological total tau or phosphorylated tau. Results The Alzheimer's disease CSF profile, and pathological levels of amyloid beta 1‐42, were associated with a more rapid decline in MMSE (2.2 [P < 0.05] and 2.9 points difference [P < 0.01], respectively). Higher total tau values showed a trend toward association without statistical significance (2.0 points difference; P = 0.064), whereas phosphorylated tau was not associated with decline. Conclusions Reduced levels of CSF amyloid beta 1‐42 were associated with more rapid cognitive decline in Lewy body dementia patients. Future prospective studies should include larger samples, centralized CSF analyses, longer follow‐up, and biomarker‐pathology correlation. © 2016 International Parkinson and Movement Disorder Society